2020
DOI: 10.1021/acsomega.0c03975
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting CDK6 Activity by Quercetin Is an Attractive Strategy for Cancer Therapy

Abstract: Cyclin-dependent kinase 6 (CDK6) is a potential drug target that plays an important role in the progression of different types of cancers. We performed in silico and in vitro screening of different natural compounds and found that quercetin has a high binding affinity for the CDK6 and inhibits its activity with an IC 50 = 5.89 μM. Molecular docking and a 200 ns whole atom simulation of the CDK6-quercetin complex provide insights into the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 84 publications
1
17
0
1
Order By: Relevance
“…Que can induce G2/M cell cycle arrest in numerous cancer cell lines through the regulation of cycle related molecules such as cyclinB1, MiR-34a, and p53 (Lou et al., 2015 ). In addition, Que displays a high binding affinity to CDK6 and downregulates its expression in A549, arresting cell cycle and reducing cell viability and colony formation (Yousuf et al., 2020 ). In this study, free Que treatment showed a slight arrest in G2/M, about 2.84% and 5.28% at concentration of 5 and 10 µg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Que can induce G2/M cell cycle arrest in numerous cancer cell lines through the regulation of cycle related molecules such as cyclinB1, MiR-34a, and p53 (Lou et al., 2015 ). In addition, Que displays a high binding affinity to CDK6 and downregulates its expression in A549, arresting cell cycle and reducing cell viability and colony formation (Yousuf et al., 2020 ). In this study, free Que treatment showed a slight arrest in G2/M, about 2.84% and 5.28% at concentration of 5 and 10 µg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin (3,3′,4′5,7-pentahydroxyflavone), classified as a flavonoid, is found in many plants and foods consumed by humans such as apples, berries, grape, onions, green tea, and Ginkgo biloba. A polyphenolic compound, quercetin, presents a variety of physiological benefits, including anti-oxidant, anti-inflammatory, anti-cancerous, anti-viral, anti-bacterial, and immunomodulatory [49] , [111] , [112] , [113] , [114] , [115] . Studies including in vitro system and in vivo animal model have shown the immune-modulating effects of quercetin, such as an increase in the chemotaxis motion of neutrophil cells, phagocytosis, lytic activity and proliferation of different immune cells.…”
Section: Quercetin Mediated Inhibition Of 3cl Protease Activity and Viral Entrymentioning
confidence: 99%
“…CDK6 was cloned, expressed, and purified by following our previously published protocols 78,79 . The purity of the recombinant CDK6 protein was checked on 12% sodium dodecyl sulfate‐polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%